Optical polyester film and preparation method thereof
Through the melt coextrusion and bidirectional stretching process of polyester slices and opening agent, an optimized optical polyester film is formed, which solves the water absorption and birefringence problems of TAC film and PET film in humid and hot environments, and improves the liquid crystal display and OLED The display effect and mechanical properties of the screen.
Patent Information
- Application Number
- CN202411347695.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing TAC films are prone to absorb water in humid and hot environments, resulting in changes in the size of the liquid crystal display and light leakage and rainbow patterns. The PET film has birefringence problems in polarizer applications, affecting the display effect.
Polyester slices and opening agent are melted and co-extruded at a specific temperature, and bidirectional stretching is performed after rapid cooling, controlling the optical axis angle and phase difference to form an optimized optical polyester with A/B/A or A/B/C structure. Thin film, inhibits rainbow pattern and birefringence.
The orientation and phase difference of optical polyester films are improved, effectively solving the rainbow pattern and optical axis angle problems in liquid crystal displays and OLED screens, and improving the display effect and mechanical performance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical polyester films, in particular to an optical polyester film and a preparation method thereof. Background Art
[0002] LCD-TFT / OLED is a new display technology that has shown explosive growth in recent years. As an optical film of liquid crystal display technology, it has changed with each passing day with the development of display technology. Recently, with the development trend of large-size TV, liquid crystal displays have put forward higher requirements for polarizers, which are the components of screens: such as higher mechanical properties and lower hygroscopicity. As the core material, TAC film is processed from wood pulp or cotton products. It is not only easy to absorb moisture, but also affects the arrangement of iodine dyes in the polarizer PVA, causing light leakage, egg mura and other bad patterns on the display. In addition, the size of TAC film changes greatly in a hot and humid environment, causing butterfly patterns or panel bending on the display. Therefore, it is urgent to develop PVA protective materials that can replace TAC film. At present, COP film and PMMA film have been gradually replaced by TAC in the market, but COP is more expensive than TAC, and PMMA is more brittle, so it is easy to break whether it is at the raw material film making end or during the lamination process of polarizer manufacturers.
[0003] On the other hand, in the prior art, PET film is mainly used in the backlight module of liquid crystal display as low value-added products such as prism film, brightness enhancement film, polarizer release film, protective film, etc. It is mainly used in the backlight module as low value-added products such as prism film, brightness enhancement film, polarizer release film, protective film, etc. The use of polyester such as PET film as a partial substitute for TAC has become a new research direction.
[0004] However, although polyester materials such as PET film have the advantages of high mechanical strength, high transparency, good dimensional stability, and low water permeability, they have always had the problem of rainbow patterns when used as polarizer PVA protective film materials due to the problem of birefringence. The rainbow patterns will affect the visual effect of the LCD TV screen and cause color deviation. Similarly, when used as an OLED fingerprint unlocking mobile phone protector, the optical axis angle and rainbow pattern problems of the PET film will cause distortion of the fingerprint collection image, thereby affecting the unlocking function of the mobile phone.
[0005] In summary, the preparation of an optical polyester film is of great significance. Summary of the invention
[0006] The object of the present invention is to provide an optical polyester film and a preparation method thereof to solve the problems raised in the above background technology.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing an optical polyester film comprises the following steps: Step 1: Using polyester chips and anti-blocking agent as A layer material; using polyester chips as B layer material; melt-coextruding A layer material and B layer material at 265°C~295°C, and rapidly cooling to obtain a multi-layer polyester sheet; Step 2: biaxially stretching and heat-setting the multi-layer polyester sheet in sequence to obtain an optical polyester film.
[0008] More optimally, the structure of the multi-layer polyester sheet is an A / B / A structure.
[0009] In this process, the extrusion structure can be an A / B / A structure, wherein the A / B / A structure has the B layer as the core layer, which is mainly polyester glossy slices, such as Sinopec FG600 / FG604, etc., and the A layer material is added with an opening agent. The function of adding the opening agent is mainly to form small protrusions on the surface of the film to prevent vacuum from forming between the film layers, resulting in uneven winding; the extrusion structure can also be an A / B / C structure. The corresponding A / B / C structure uses 3 extruders, and the A / C layers can be the same or different, so opening agents with different compositions or different particle sizes can be added to the A / C layers.
[0010] More optimally, the biaxial stretching process is: the multilayer polyester sheet is longitudinally stretched at a temperature of 70°C to 130°C, with a longitudinal stretching ratio of 1 to 3.3 times, and transversely stretched at a temperature of 85°C to 150°C, with a transverse stretching ratio of 3.8 to 6 times; the ratio of the transverse stretching ratio to the longitudinal stretching ratio is 1.2 to 6.
[0011] In the scheme, when the ratio of the transverse stretching ratio to the longitudinal stretching ratio (TD / MD) is larger, it is easier to form a smaller optical axis angle and a larger phase difference (R0). However, when the stretching ratio TD / MD becomes larger, the film-forming property of the optical polyester film becomes worse: the thickness uniformity becomes worse and stretching spots occur. The study found that a larger TD / MD stretching ratio ratio can be obtained by improving the tensile ductility of the polyester chips and reducing the tensile stress.
[0012] More optimally, the angle between the optical axis of the optical polyester film and the transverse stretching direction is 0°~6° or 84°~90°; the phase difference (R0) of the optical polyester film is >8000nm.
[0013] Among them, the following problems exist in the traditional biaxially stretched polyester film: (1) Its optical axis angle range is very large, ranging from 0° to 50°; and the circular polarizer with an optical axis angle of 45° is attached to the OLED screen. Because the molecular chain of polyester films such as BOPET has an optical rotation effect, it will destroy the polarization state; (2) When the optical axis angle of the polyester film cannot be consistent with the optical axis angle of the polarizer, the original light path is destroyed by the BOPET film. In addition, the rainbow pattern generated on the surface of the polyester film causes the fingerprint chip to be unable to collect the real fingerprint image, resulting in poor fingerprint unlocking sensitivity or even no unlocking at all; (3) When BOPET film is used on the polarizer of the liquid crystal display, due to the serious birefringence problem of BOPET film after biaxial stretching, the transmittance of light of different wavelengths is inconsistent, thus forming a rainbow aperture.
[0014] Therefore, in the scheme, by controlling the biaxial stretching process, when the angle between the optical axis of the PET film and the TD direction is 0°~6° or 84°~90°, and the phase difference of the optical polyester film reaches more than 8000nm, the problems caused by the traditional biaxially stretched polyester film can be effectively suppressed.
[0015] Preferably, the heat setting process is: first setting at a temperature of 180°C to 250°C, and then cooling at 180°C.
[0016] More optimally, the polyester chips are pre-dried before use, and the drying process is: drying the polyester chips at 100° C. to 180° C. for 2 to 6 hours, and controlling the moisture content to be <200 ppm.
[0017] In the scheme, the drying temperature is preferably 150°C to 170°C, the moisture content of the polyester chips is preferably <100ppm, and the moisture content of the polyester chips is most preferably <50ppm.
[0018] More optimally, the polyester chips include one or both of polyethylene terephthalate and polyethylene 2,6-naphthalate.
[0019] In the embodiment, the intrinsic viscosity of the polyester chips is usually in the range of 0.5 dl / g to 0.8 dl / g, preferably in the range of 0.55 to 0.75 dl / g, and more preferably in the range of 0.6 to 0.645 dl / g.
[0020] In the scheme, in order to remove foreign matter in the polyester chip raw material and prevent defects in the optical polyester film, it is preferred to use high-efficiency filtration during melt extrusion, and the filter pore size of the filter equipment is selected to be less than 25 μm, more preferably 15 μm.
[0021] More optimally, the opening agent includes one or more of silicon dioxide, barium sulfate, and calcium carbonate; the addition ratio of the opening agent in the A layer material accounts for 300ppm~1500ppm of the A layer.
[0022] In the scheme, the particle size of the opening agent is usually ≤5 μm, preferably 0.2 μm~3 μm.
[0023] In the scheme, the particle size and content of the opening agent affect the anti-sticking performance and appearance of the optical polyester film. When the particle size is too large, point defects will be formed, and when the particle size is too small, the anti-sticking performance will deteriorate. At the same time, when the content of the opening agent is too high, the overall transmittance will be reduced; in the scheme, the opening agent can be distributed in the entire thickness direction, or only distributed in the surface layer of the film; in order to improve the transparency of the film, it is preferred to add the particles to the surface layer; when an A / B / A structure extruder is selected, the opening agent is added to two surface layers, and when an A / B / C structure extruder is selected, the opening particles are added to any one or two layers of the A layer or the C layer; when the opening agent is added to only one surface layer, while ensuring the opening property, the overall haze and the roughness of the other side are reduced, which can meet the requirements of low haze and low roughness of the optical film.
[0024] In addition, in the preparation of the optical polyester film, a UV absorber can be added to the polyester slice to improve the anti-ultraviolet function of the optical polyester film. The UV absorber can be a benzophenone-based UV absorber, a salicylic acid-based UV absorber, a benzotriazole-based UV absorber, or the like.
[0025] Compared with the prior art, the present application has the following beneficial effects: (1) Compared with traditional polyester films, the optical polyester film prepared in this application has higher orientation degree and phase difference, and can be well applied in the fields of LCD and OLED displays.
[0026] (2) In order to solve the rainbow streak problem of biaxially stretched polyester film (such as PET film), the scheme uses a specific characteristic viscosity and a limited biaxial stretching process to effectively control the angle between the optical axis angle of the optical polyester film and the TD direction to be between 0° and 6°, or between 84° and 90°, and at the same time makes the phase difference (R0) of the optical polyester film > 8000nm, thereby effectively suppressing the optical axis angle and rainbow streak problems of the polyester film. DETAILED DESCRIPTION
[0027] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.
[0028] Embodiment 1
[0029] Step 1: drying polyester chips with an intrinsic viscosity of 0.675 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; the layer A material and the layer B material are melt-coextruded at 280° C., and rapidly cooled to below the glass transition temperature Tg at 25° C. to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in the layer A material is 500 ppm; Step 2: The multilayer polyester sheet is stretched longitudinally (MD) 3.3 times at 83°C, and then stretched transversely (TD) 3.8 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0030] Embodiment 2 is based on embodiment 1, and adopts A / B / C structure; Step 1: Dry the polyester chips with an intrinsic viscosity of 0.675 dl / g at 160°C for 3 hours to remove moisture and pre-crystallize, dry to a moisture content of ≤25ppm, and uniformly mix with silica to obtain layer A material; the polyester chips are layer B material; use 3 extruders to melt co-extrude layer A material, layer B material, and layer C material (only the same amount of silica opening agent is added to layer A, and layer C and layer B are pure PET polyester) at 280°C, and rapidly cool to below the glass transition temperature Tg point at 25°C to obtain a multi-layer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silica added to layer A is 500ppm; Step 2: The multilayer polyester sheet is stretched longitudinally (MD) 3.3 times at 83°C, and then stretched transversely (TD) 3.8 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0031] Example 3 is based on Example 1, and the longitudinal stretching ratio is 2.8 times; Step 1: drying polyester chips with an intrinsic viscosity of 0.675 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; the layer A material and the layer B material are melt-coextruded at 280° C., and rapidly cooled to below the glass transition temperature Tg at 25° C. to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in the layer A material is 500 ppm; Step 2: The multilayer polyester sheet is stretched longitudinally (MD) 2.8 times at 83°C, and then stretched transversely (TD) 3.8 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0032] Example 4 is based on Example 1, and the longitudinal stretching ratio is 2.5 times; Step 1: drying polyester chips with an intrinsic viscosity of 0.675 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; the layer A material and the layer B material are melt-coextruded at 280° C., and rapidly cooled to below the glass transition temperature Tg at 25° C. to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in the layer A material is 500 ppm; Step 2: The multilayer polyester sheet is stretched longitudinally (MD) 2.5 times at 83°C, and then stretched transversely (TD) 3.8 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0033] Example 5 is based on Example 4, and the transverse stretching ratio is 4.6 times; Step 1: drying polyester chips with an intrinsic viscosity of 0.675 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; the layer A material and the layer B material are melt-coextruded at 280° C., and rapidly cooled to below the glass transition temperature Tg at 25° C. to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in the layer A material is 500 ppm; Step 2: The multilayer polyester sheet is stretched longitudinally (MD) 2.5 times at 83°C, and then stretched transversely (TD) 4.6 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0034] Example 6 is based on Example 5, the longitudinal stretching ratio is 2 times, and the thickness of the optical polyester film is 50 μm; Step 1: drying polyester chips with an intrinsic viscosity of 0.675 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; the layer A material and the layer B material are melt-coextruded at 280° C., and rapidly cooled to below the glass transition temperature Tg at 25° C. to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in the layer A material is 500 ppm; Step 2: The multilayer polyester sheet is stretched longitudinally (MD) by 2 times at 83°C, and then stretched transversely (TD) by 4.6 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 50 μm.
[0035] Example 7 is based on Example 6, and the longitudinal stretching ratio is 1.5 times; Step 1: drying polyester chips with an intrinsic viscosity of 0.675 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; the layer A material and the layer B material are melt-coextruded at 280° C., and rapidly cooled to below the glass transition temperature Tg at 25° C. to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in the layer A material is 500 ppm; Step 2: The multilayer polyester sheet is longitudinally stretched (MD) 1.5 times at 83°C, and then transversely stretched (TD) 4.6 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 50 μm.
[0036] Example 8 is based on Example 7, the thickness of the optical polyester film is 100 μm; Step 1: drying polyester chips with an intrinsic viscosity of 0.675 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; the layer A material and the layer B material are melt-coextruded at 280° C., and rapidly cooled to below the glass transition temperature Tg at 25° C. to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in the layer A material is 500 ppm; Step 2: The multilayer polyester sheet is longitudinally stretched (MD) 1.5 times at 83°C, and then transversely stretched (TD) 4.6 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0037] Example 9 is based on Example 8, with a longitudinal stretching ratio of 1.3 times, an A / B / C three-layer structure, and an anti-blocking agent is only added to the A layer; Step 1: Dry the polyester chips with an intrinsic viscosity of 0.675 dl / g at 160°C for 3 hours to remove moisture and pre-crystallize, dry to a moisture content of ≤25ppm, and uniformly mix with silica to obtain layer A material; the polyester chips are layer B material; use 3 extruders to melt co-extrude layer A material, layer B material, and layer C material (only the same amount of silica opening agent is added to layer A, and layer C and layer B are pure PET polyester) at 280°C, and rapidly cool to below the glass transition temperature Tg point at 25°C to obtain a multi-layer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silica added to layer A is 500ppm; Step 2: The multilayer polyester sheet is longitudinally stretched (MD) 1.3 times at 83°C, and then transversely stretched (TD) 4.6 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0038] Example 10 is based on Example 9, adopting A / B / A structure, the A layer has an opening agent content of 300ppm, and after longitudinal drawing, a primer material is coated on one side; Step 1: drying polyester chips with an intrinsic viscosity of 0.675 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; melt co-extruding layer A material and layer B material at 280° C., rapidly cooling to below the glass transition temperature Tg point at 25° C., to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate; Step 2: The multi-layer polyester sheet is stretched longitudinally (MD) 1.3 times at 83°C, and a layer of primer material is coated on one side through a gravure roll or a wire rod. The function of the primer material is mainly to improve the transparency of the film. Then, it is stretched transversely (TD) 4.6 times at 115°C, first fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100μm.
[0039] The primer material is composed of the following parts: 4% acrylic acid or polyurethane or polyester resin, 0.8% epoxy curing agent, and 1% sulfonate, by mass.
[0040] Example 11 is based on Example 10, and after longitudinal stretching, a primer material is coated on both sides of the film; Step 1: Dry the polyester chips with an intrinsic viscosity of 0.675 dl / g at 160°C for 3 hours to remove moisture and perform pre-crystallization, dry to a moisture content of ≤25ppm, and evenly mix with silicon dioxide to obtain layer A material; the polyester chips are layer B material; the layer A material and the layer B material are melt-coextruded at 280°C, and rapidly cooled to below the glass transition temperature Tg point at 25°C to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate; the anti-blocking agent content in layer A is 300ppm.
[0041] Step 2: The multi-layer polyester sheet is stretched longitudinally (MD) 1.3 times at 83°C, and a layer of primer material is coated on both sides through a gravure roll or a wire rod. The function of the primer material is mainly to improve the transparency of the film. Then, it is stretched transversely (TD) 4.6 times at 115°C, first fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100μm.
[0042] The primer material is composed of the following parts: 4% acrylic acid or polyurethane or polyester resin, 0.8% epoxy curing agent, and 1% sulfonate, by mass.
[0043] Example 12 Based on Example 1, the intrinsic viscosity of the polyester chips is 0.645 dl / g; Step 1: drying polyester chips with an intrinsic viscosity of 0.645 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; melt co-extruding layer A material and layer B material at 280° C., rapidly cooling to below the glass transition temperature Tg point at 25° C., to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in layer A material is 500 ppm; Step 2: The multilayer polyester sheet is stretched longitudinally (MD) 3.3 times at 83°C, and then stretched transversely (TD) 3.8 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0044] Example 13 Based on Example 8, the intrinsic viscosity of the polyester chips is 0.645 dl / g; Step 1: drying polyester chips with an intrinsic viscosity of 0.645 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; melt co-extruding layer A material and layer B material at 280° C., rapidly cooling to below the glass transition temperature Tg point at 25° C., to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in layer A material is 500 ppm; Step 2: The multilayer polyester sheet is longitudinally stretched (MD) 1.5 times at 83°C, and then transversely stretched (TD) 4.6 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0045] Example 14 Based on Example 12, the intrinsic viscosity of the polyester chips is 0.6 dl / g; Step 1: drying polyester chips with an intrinsic viscosity of 0.6 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; the layer A material and the layer B material are melt-coextruded at 280° C., and rapidly cooled to below the glass transition temperature Tg at 25° C. to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in the layer A material is 500 ppm; Step 2: The multilayer polyester sheet is stretched longitudinally (MD) 3.3 times at 83°C, and then stretched transversely (TD) 3.8 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0046] Example 15 Based on Example 13, the intrinsic viscosity of the polyester chips is 0.6 dl / g; Step 1: drying polyester chips with an intrinsic viscosity of 0.6 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; the layer A material and the layer B material are melt-coextruded at 280° C., and rapidly cooled to below the glass transition temperature Tg at 25° C. to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in the layer A material is 500 ppm; Step 2: The multilayer polyester sheet is longitudinally stretched (MD) 1.5 times at 83°C, and then transversely stretched (TD) 4.6 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0047] Example 16 is based on Example 14: the intrinsic viscosity of the polyester chips is 0.55 dl / g; Step 1: drying polyester chips with an intrinsic viscosity of 0.55 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; melt co-extruding layer A material and layer B material at 280° C., rapidly cooling to below the glass transition temperature Tg point at 25° C., to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in layer A material is 500 ppm; Step 2: The multilayer polyester sheet is stretched longitudinally (MD) 3.3 times at 83°C, and then stretched transversely (TD) 3.8 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0048] Example 17 is based on Example 15: the intrinsic viscosity of the polyester chips is 0.55 dl / g; Step 1: drying polyester chips with an intrinsic viscosity of 0.55 dl / g at 160° C. for 3 hours to remove moisture and pre-crystallize, drying to a moisture content of ≤25 ppm, and uniformly mixing with silicon dioxide to obtain layer A material; the polyester chips are layer B material; melt co-extruding layer A material and layer B material at 280° C., rapidly cooling to below the glass transition temperature Tg point at 25° C., to obtain a multilayer polyester sheet; wherein the polyester chips are polyethylene terephthalate, and the content of silicon dioxide added in layer A material is 500 ppm; Step 2: The multilayer polyester sheet is longitudinally stretched (MD) 1.5 times at 83°C, and then transversely stretched (TD) 4.6 times at 115°C, firstly fixed at 230°C, and then cooled at 180°C to obtain an optical polyester film with a thickness of 100 μm.
[0049] Detection experiment: Evaluation indicators and methods: (1) Phase difference: R0 is calculated as R0=(nx-ny)×d; Among them, R0 represents the phase difference of the optical polyester film. The American Axoscan phase difference measuring instrument is used to take samples every 100 mm along the direction perpendicular to the width, and the refractive index and sample thickness are brought into the measuring instrument to measure the phase difference R0; Wherein, nx is the refractive index in the direction of the maximum refractive index in the film plane, ny is the refractive index perpendicular to the nx direction, and d is the thickness of the film; the refractive indices nx and ny in the plane of the optical polyester film were measured using an Abbe refractometer (manufactured by ATAGO CO., LTD, NAR-4T) at a wavelength of 589 nm.
[0050] (2) Orientation angle: Using the Oji Metrology KOBRA-WPR optical property measuring machine, samples were taken every 100 mm along the direction perpendicular to the width and placed on the instrument measuring table to measure the optical axis angle of the sample; the angle between the optical axis angle and the longitudinal stretching (TD) direction was between 0° and 6° or between 84° and 90°.
[0051] (3) Transmittance: Use NDH 4000 Haze meter to measure the transmittance of optical polyester film at intervals of 100 mm along the direction perpendicular to the width.
[0052] (4) Haze: Use NDH 4000 Haze meter to measure the haze every 100 mm along the direction perpendicular to the width.
[0053] (5) Thickness: Use a Mitutoyo thickness gauge to measure the thickness at intervals of 100 mm along the direction perpendicular to the width of the optical polyester film. (6) Evaluation method for rainbow patterns: Cut the test optical polyester film into A4 or other size and shape samples along the MD and TD (MD: longitudinal stretching, TD: transverse stretching) directions, place the sample on a backlight, place a polarizer on the backlight, place the sample on the polarizer, and then place another polarizer on the sample. The absorption axes of the upper and lower polarizers must be kept at a 90° orthogonal state; then rotate the sample to confirm whether rainbow patterns occur during the rotation process.
[0054] Examples Intrinsic viscosity Vertical pull ratio Horizontal pulling ratio Thickness(μm) structure Primer material Transmittance (%) haze(%) R0(nm) Rainbow pattern Appearance 1 0.675 3.3 3.8 100 A / B / A none 88.2 1.4 3217 ╳ ○ 2 0.675 3.3 3.8 100 A / B / C none 88.7 1.1 3298 ╳ ○ 3 0.675 2.8 3.8 100 A / B / A none 88.3 1.5 3651 ╳ ○ 4 0.675 2.5 3.8 100 A / B / A none 88.4 1.4 3973 ╳ ○ 5 0.675 2.5 4.6 100 A / B / A none 88.5 1.5 4319 ╳ △ 6 0.675 2 4.6 50 A / B / A none 88.4 1.4 3004 ╳ △ 7 0.675 1.5 4.6 50 A / B / A none 88.2 1.4 5154 △ ╳ 8 0.675 1.5 4.6 100 A / B / A none 88.8 1.4 8807 ○ ╳ 9 0.675 1.3 4.6 100 A / B / C none 89.1 1.0 8930 ○ ╳ 10 0.675 1.3 4.6 100 A / B / A Single-sided 90.8 1.2 8906 ○ ╳ 11 0.675 1.3 4.6 100 A / B / A Double-Sided 92.3 1.2 8911 ○ ╳ 12 0.645 3.3 3.8 100 A / B / A none 88.2 1.4 3105 ╳ ○ 13 0.645 1.5 4.6 100 A / B / A none 88.3 1.5 8841 △ △ 14 0.6 3.3 3.8 100 A / B / A none 88.3 1.4 3307 ╳ ○ 15 0.6 1.5 4.6 100 A / B / A none 88.1 1.4 9028 ○ ○ 16 0.55 3.3 3.8 100 A / B / A none 88.3 1.4 3219 ╳ △ 17 0.55 1.5 4.6 100 A / B / A none 88.2 1.4 8986 ○ ╳ Table 1 Note: Rainbow pattern ╳ indicates severe rainbow pattern, △ indicates visible rainbow pattern, ○ indicates no rainbow pattern. Appearance ╳ indicates very poor uneven thickness of pattern, △ indicates moderate uneven thickness of pattern, ○ indicates no pattern and uneven thickness.
[0055] Conclusion: By studying the specific intrinsic viscosity and the limited biaxial stretching process, the angle between the optical axis angle of the optical polyester film and the TD direction can be effectively controlled to be 0°~6°, or 84°~90°, and the phase difference (R0) of the optical polyester film surface can be made greater than 8000nm. Therefore, the optical axis angle and rainbow pattern problems of the polyester film can be effectively suppressed. It is found that among Examples 1 to 17, the best solution is Example 15.
[0056] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.
Claims
1. A method for preparing an optical polyester film, characterized in that: The steps include: Step 1: Using polyester chips and anti-blocking agent as A layer material; using polyester chips as B layer material; melt-coextruding A layer material and B layer material at 265°C~295°C, and rapidly cooling to obtain a multi-layer polyester sheet; Step 2: biaxially stretching and heat-setting the multi-layer polyester sheet in sequence to obtain an optical polyester film.
2. The method for preparing an optical polyester film according to claim 1, characterized in that: The optical polyester film has an angle between its optical axis and the transverse stretching direction of 0° to 6° or 84° to 90°; and the optical polyester film has a phase difference R0 of ≥8000nm.
3. The method for preparing an optical polyester film according to claim 1, characterized in that: The structure of the multi-layer polyester sheet is A / B / A structure.
4. The method for preparing an optical polyester film according to claim 1, characterized in that: The biaxial stretching process is as follows: the multilayer polyester sheet is longitudinally stretched at a temperature of 70°C to 130°C with a longitudinal stretching ratio of 1 to 3.3 times, and transversely stretched at a temperature of 85°C to 150°C with a transverse stretching ratio of 3.8 to 6 times; the ratio of the transverse stretching ratio to the longitudinal stretching ratio is 1.2 to 6.
5. The method for preparing an optical polyester film according to claim 1, characterized in that: The heat setting process is: first setting at a temperature of 180°C to 250°C, and then cooling at 180°C.
6. The method for preparing an optical polyester film according to claim 1, characterized in that: The intrinsic viscosity of polyester chips is 0.6~0.645dl / g.
7. The method for preparing an optical polyester film according to claim 1, characterized in that: The polyester chips are pre-dried before use, and the drying process is: drying the polyester chips at 100° C. to 180° C. for 2 to 6 hours, and controlling the water content to be less than 200 ppm.
8. The method for preparing an optical polyester film according to claim 1, characterized in that: The polyester chips include one or two of polyethylene terephthalate and polyethylene-2,6-naphthalate.
9. The method for preparing an optical polyester film according to claim 1, characterized in that: The opening agent includes one or more of silicon dioxide, barium sulfate, and calcium carbonate; the addition ratio of the opening agent in the A layer material is 300ppm~1500ppm, and the particle size of the opening agent is 0.2μm~3μm.
10. The optical polyester film prepared by the method for preparing an optical polyester film according to any one of claims 1 to 9, characterized in that: The thickness of the optical polyester film is 50 μm to 100 μm.
Citation Information
Patent Citations
Polyester film, polarising plate, and image display device
CN105308486A
Low-rainbow-line polyester film and preparation method thereof
CN109943027A
Polyester multilayer film and preparation method thereof
CN114466737A
High-light-transmittance polyester film and manufacturing method thereof
CN114702789A
Laminated polyester film for cathode-ray tube
JP1998106455A
